Smart classrooms and education outcomes: Evidence from Rwanda - Aimable Nsabimana; Muthoni Nganga; Christine Niyizamwiyitira (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
In this study, we explore the impact of a smart classroom (SCM) programme on student performance in science subjects in a high-stakes national exam for middle-high school students in Rwanda. To do this, we leverage plausibly exogenous variations in programme exposure induced by the staggered implementation of the programme across schools and students. Overall, the study finds a positive effect of the programme on student performance. Specifically, the results show that the SCM programme has positive and significant effects on student performance in physics, biology, and geography, albeit small in magnitude. The study, however, did not reveal any effects on mathematics and chemistry. We find larger effects in government-aided schools, for girls, and for younger students. Our results also indicate that while classroom technology can enhance learning, such effects may only be realized after a long exposure period.
Keywords: I21; I26; O12; 330; secondary education; smart classrooms; Rwanda